Prevalence, awareness, characteristics, and health outcomes associated with COPD at-risk status among adults in Japan. (3rd July 2016) - Omori, Hisamitsu; Yoshimoto, Daisuke; Kumar, Maya; Goren, Amir
Abstract : Objectives : We examined the prevalence of chronic obstructive pulmonary disease (COPD) diagnosed and at-risk status, and public awareness of COPD among adults in Japan, as well as respondent characteristics and health outcomes compared with controls. Methods : Regression models used 2012 National Health and Wellness Survey in Japan data to compare COPD-diagnosed, at-risk, and healthy adults (aged ≥18) on demographics, health behaviors, health-related quality of life (HRQoL), productivity and healthcare resource use. Results : Among n = 29, 978 respondents, diagnosed COPD prevalence was 0.9%; 26.9% were at-risk. Relative to controls, those at-risk and diagnosed with COPD had significantly greater healthcare resource use, with lower productivity and HRQoL. Fewer than 20% of respondents were aware of COPD. Conclusions : Over 25% of adult Japanese respondents were at-risk for COPD and had health outcomes impairments relative to controls. Efforts to increase awareness among the general public are needed.